HIV-SPECIFIC SECRETORY IGA IN BREAST MILK OF HIV-POSITIVE MOTHERS IS NOT ASSOCIATED WITH PROTECTION AGAINST HIV TRANSMISSION AMONG BREAST-FED INFANTS - Kuhn, Louise (2006)
OBJECTIVES: To test whether secretory immunoglobulin A (sIgA) to human immunodeficiency virus (HIV) antigens in breast milk of HIV-positive women is associated with protection against HIV transmission among breast-fed infants. STUDY DESIGN: Nested, case-control design in which HIV-specific sIgA was measured in breast milk collected from 90 HIV-positive women enrolled in a study in Lusaka, Zambia. Milk samples were selected to include 26 HIV-positive mothers with infected infants (transmitters) and 64 mothers with uninfected infants (nontransmitters). RESULTS: HIV-specific sIgA was detected more often in breast milk of transmitting mothers (76.9%) than in breast milk of nontransmitting mothers (46.9%, P = .009). There were no significant associations between HIV-specific sIgA in breast milk and other maternal factors, including HIV RNA quantities in breast milk, CD4 count, and plasma RNA quantities. CONCLUSIONS: HIV-specific sIgA in breast milk does not appear to be a protective factor against HIV transmission among breast-fed infants.